Dificuldades no aleitamento materno durante o puerpério - Carine Vieira Bicalho (2023)
Introduction: Breastfeeding (BF) is an important factor in health promotion because it is an action of protection, bonding, affection and nutrition for the child. BF is the most economical and effective intervention for reducing child morbidity and mortality, when practiced according to the recommendation of the World Health Organization: exclusively in the first six months and up to two years or more in a complementary way. Breastfeeding is much more than nourishing the child, it is a process that involves deep interaction between mother and child, in addition to promoting numerous benefits for both. In addition to the benefits for the child and the mother, it is important to emphasize the negative impacts that non-breastfeeding has on the environment, since, unlike formulas and artificial milk, breast milk is a “renewable” food, produced and supplied without pollution, packaging and waste. Despite the beneficial effects of exclusive breastfeeding, the early interruption of this practice remains, in Brazil, one of the most important public health problems. The evaluation of the mother-infant dyad is important in order to identify if there are any difficulties related to breastfeeding and in which situation it is found. Based on this identification, the intervention proposal can be better planned. Objective: to characterize the difficulties faced by puerperal women assisted at the Breastfeeding Outpatient Clinic of the Vila Maria Health Center (Belo Horizonte, Minas Gerais) according to the puerperal period, in addition to analyzing the association between the presence of complaints and prenatal data, maternal, child and breastfeeding. Methods: observational cross-sectional study, carried out with secondary data from the Breastfeeding Outpatient Clinic of the Vila Maria Health Center. The medical records of all puerperal women (n=269) attended at the aforementioned outpatient clinic, from August 2019 (beginning of its activities) to July 2022, were analyzed. Data were collected through an existing protocol at the outpatient clinic that contains 11 items on identification data, 14 on the puerperal woman's assessment, 15 on the child's assessment and three items on the assessment of the mother-infant dyad. Descriptive analyzes and univariate and multivariate logistic regression of the data were performed. The magnitude of associations was assessed by odds ratios. Results: it was observed that the period in which the mothers attended at the outpatient clinic had more complaints about breastfeeding was in the immediate puerperium, referring to breast problems and pain when breastfeeding. In the late puerperium, there was no difference regarding greater or lesser difficulty. On the other hand, mothers who were in the remote puerperium period reported in greater proportion that their children had difficulty gaining weight. According to the univariate analysis, variable variables accompanied by the fact that the mother complained about breastfeeding: cesarean section, not breastfeeding in the first hour of life, having altered breast and breast tissue, not being exclusively breastfed, having difficulty in latching on, inadequate positioning of the puerperal woman, inadequate positioning of the child, using a pacifier or bottle nipple, having difficulty in handling/adjusting the position and needing to return to the health center. In the final model of the multivariate analysis, statistically significant results were observed for the presence of breastfeeding complaints and: altered aspect of the breasts, not having breastfed in the first hour of life, possibly incorrect latching, having had difficulties in handling/adjusting the positioning and need back to health center. Conclusion: mothers assisted at the Breastfeeding Outpatient Clinic of the Vila Maria Health Center have more complaints about breastfeeding in the immediate puerperium, referring to breast problems and pain when breastfeeding. The presence of breastfeeding complaints was related to: altered appearance of the breasts, not having breastfed in the first hour of life, incorrect latching, having had difficulties in managing/adjusting the position and needing to return to the health center